Growth regimes of populist governments: A comparative study on Hungary and Poland - Julia Kühnast (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
This paper aims to contribute to the debate of post-Keynesian growth models and Comparative Political Economy (CPE) by investigating the relationship between the changes in demand and growth regimes and the establishment of right-wing populist governments in Poland and Hungary after the Global Financial Crisis (GFC). In both countries, these parties established a system that lays a stronger focus on economic nationalism and the role of the state to reduce foreign influence. Both economies are currently in a transition phase in which their old, neoliberal regimes are slowly changing, but they have not yet completely abandoned neoliberalism. In both countries, post-GFC economic policies have led to changes in the growth regimes and increased the importance of the export sector. It was mainly the demands of domestic capitalists that constituted the social base for these changes.
Keywords: E12; E65; F40; F43; G01; O57; 330; Growth regimes; Populism; Comparative Political Economics